Research on the factors impact on the cohesion in higher education training between universities and enterprises: case study in Danang - Anh Hoang, Ngo; Hanh, Nguyen Thi (VNU Journal of Science: Education Research, 2017)
Higher education plays critical role in providing human resources to society in all areas. Universities are thriving to carry out the test of training citizens to meet social needs; exploring science and technology, bringing scientific achievements into practice to serve the industrialization and modernization of the countries. However, our higher institutions have not accomplished all of these goals; we are preferring to focus on training generations of graduates with excellent results only in their academic performance, despite the increasing demands of enterprises in reality. This research studied the factors that influence the cohesion between universities and enterprises, thereby, suggesting further feasible solutions and policies strengthening this critical relationship, shifting universities education closer to practical needs, generating high-quality employees for society, producing breakthroughs in scientific research, therefore, delivering benefits to among  universities, enterprises, and society to improve linkage in geo-training in Da Nang city in particular and Central Vietnam in general.